Rancang Bangun Alat Penyekir Katup Otomatis Berbasis Microcontroller - Yuvani Oksarianti; Dedi Mulyono; Riko Saputra; Doni Saputra; Ahmad Arif (AEEJ : Journal of Automotive Engineering and Vocational Education, 2022)
Leakage of the valve in the cylinder head of the combustion engine was caused by a pile of crust attached to the valve seat, so that it interferes with the compression process and reduces engine performance. Valve Grinding Automatic System Based Microcontroller is an innovation designed for valve cleaning, works by converting electrical energy into rotational motion. Using research and development methods, this tool was developed to overcome the mechanical difficulties of adjusting manual cleaning movements by hand. The variables in this study were the dynamo rotational speed and the time required for cleaning. Based on the research, Valve Grinding Automatic System Based Microcontroller provides three choices of rotational speed of 1500 rpm, 2000 rpm and 2500 rpm with each speed requiring a cleaning time of 3 minutes, 2 minutes, and 1 minute. From the results of testing using diesel fuel, it is known that the results of cleaning the valve do not leak and have met the standard. Kebocoran katup pada cylinder head motor bakar disebabkan oleh tumpukan kerak yang melekat pada seating katup sehingga mengganggu proses kompresi dan menurunkan kinerja mesin. Alat Penyekir Katup Otomatis Berbasis Microcontroller merupakan inovasi yang dirancang untuk penyekiran katup yang bekerja dengan cara mengubah energi listrik menjadi gerak rotasi. Dengan metode research and development, alat ini dikembangkan untuk mengatasi kesulitan mekanik dalam mengatur gerakan penyekiran manual dengan tangan. Variabel dalam penelitian ini adalah kecepatan putaran dinamo dan waktu yang dibutuhkan untuk penyekiran. Berdasarkan penelitian yang dilakukan, Alat Penyekir Katup Otomatis Berbasis Microcontroller menyediakan tiga pilihan kecepatan putaran yakni 1500 rpm, 2000 rpm dan 2500 rpm dengan masing-masing kecepatan memerlukan waktu penyekiran 3 menit, 2 menit, dan 1 menit. Dari hasil pengujian dengan menggunakan solar, diketahui bahwa hasil penyekiran katup tidak mengalami kebocoran dan telah memenuhi standar.